Effect of Biological Asset Intensity, Company Size, Ownership Concentration, and Type Firm against Biological Assets - Yurniwati Yurniwati; Amsal Djunid; Frida Amelia (The Indonesian Journal of Accounting Research, 2018)
Abstract: Data from the Central Statistics Agency shows Indonesia's agricultural growth rate in the first quarter of 2016 was only 1.85%. This growth rate decreased significantly, when compared to the same quarter of 2015 which reached 4.03%. This needs to be a concern for the government, society and agricultural companies, because the agricultural sector is one of the backbones in national economic development. The purpose of this study was to examine and analyze the influence of biological assets on the intensity, size of the company, concentration of ownership and type of KAP on the disclosure of biological assets in agricultural companies listed on the Indonesia Stock Exchange for the period 2012-2015. This type of research is descriptive verification. The population in this study were all agricultural companies listed on the Indonesia Stock Exchange, where the sample was selected by purposive sampling method. Through this method 18 companies were selected. Data collection methods are documentary studies. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that the intensity of biological assets and company size has a significant positive effect on the disclosure of biological assets.Abstrak: Data Badan Pusat Statistik menunjukkan tingkat pertumbuhan pertanian Indonesia pada kuartal pertama 2016 hanya 1,85%. Tingkat pertumbuhan ini menurun secara signifikan, jika dibandingkan dengan kuartal yang sama dari tahun 2015 yang mencapai 4.03%. Ini perlu menjadi perhatian bagi pemerintah, masyarakat dan perusahaan pertanian, karena sektor pertanian adalah salah satu tulang punggung dalam pembangunan ekonomi nasional. Tujuan penelitian ini untuk menguji dan menganalisis pengaruh aset biologis terhadap intensitas, ukuran perusahaan, konsentrasi kepemilikan dan jenis KAP pada pengungkapan aset biologis pada perusahaan pertanian yang terdaftar di Bursa Efek Indonesia periode 2012-2015. Jenis penelitian ini adalah verifikasi deskriptif. Populasi dalam penelitian ini adalah semua perusahaan pertanian yang terdaftar di Bursa Efek Indonesia, dimana sampel dipilih dengan metode purposive sampling. Melalui metode ini 18 perusahaan dipilih. Metode pengumpulan data adalah studi dokumenter. Metode analisis yang digunakan dalam penelitian ini adalah analisis regresi linier berganda. Hasil penelitian ini menunjukkan bahwa intensitas aset biologis dan ukuran perusahaan memiliki pengaruh positif yang signifikan terhadap pengungkapan aset biologis